Equality of Rights and Obligations: The Role and Position of Women in Politics (Study of the Interpretation of Surah An Naml verses 23-23) - Fitria, Salwa Aida; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
The equality of women's rights and obligations in politics is an issue that has long been debated, especially in the context of Islam. Surah An-Naml verses 23-24 tells the leadership of Queen Saba', which is one of the evidences in the Qur'an regarding the role of women in politics. This study aims to examine the rights, obligations, roles, and positions of women in politics through the analysis of the interpretation of Surah An-Naml verses 23-24. The method used is a thematic interpretation approach by referring to various classical and contemporary interpretations, such as Tafsir Al-Misbah, Tafsir Al-Azhar, and Tafsir Al-Maraghi. The results of the study show that Islam does not absolutely prohibit women from participating in politics, even in leadership, as long as they have the capacity and are able to carry out their mandate well. The story of Ratu Saba' illustrates how a woman can be a wise, democratic, and strategically minded leader in making decisions. This research is expected to provide an overview that Islam recognizes the role of women in politics, while still paying attention to the principles of justice, benefit, and moral responsibility. Therefore, a broader and contextual understanding of the verses of the Qur'an is needed so that there is no gender bias in interpreting the role of women in political life.